Epigenetic Mediators Between Childhood Socioeconomic Disadvantage and Mid-Life Body Mass Index: The New England Family Study. Issue 9 (November 2016) - Loucks, Eric B.; Huang, Yen-Tsung; Agha, Golareh; Chu, Su; Eaton, Charles B.; Gilman, Stephen E.; Buka, Stephen L.; Kelsey, Karl T.
ABSTRACT: Objective: Childhood socioeconomic disadvantage is associated with adulthood obesity risk; however, epigenetic mechanisms are poorly understood. This work's objective was to evaluate whether associations of childhood socioeconomic disadvantage with adulthood body mass index (BMI) are mediated by DNA methylation. Methods: Participants were 141 men and women from the New England Family Study, prospectively followed prenatally through a mean age of 47 years. Epigenomewide DNA methylation was evaluated in peripheral blood and adipose tissue obtained at adulthood, using the Infinium HumanMethylation450K BeadChip. Childhood socioeconomic status (SES) at age 7 years was assessed directly from parents' reports. Offspring adiposity was directly assessed using BMI at a mean age of 47 years. Associations of SES, DNA methylation, and BMI were estimated using least square estimators. Statistical mediation analyses were performed using joint significance test and bootstrapping. Results: Of CpG sites significant at the 25% false discovery rate level in epigenomewide methylation BMI analyses, 91 sites in men and 71 sites in women were additionally significant for SES-methylation associations ( p < .001) in adipose tissue. Many involved genes biologically relevant for development of obesity, including fatty acid synthase, transmembrane protein 88, signal transducer and activator of transcription 3, and neuritin 1. There was no evidence of epigenetic mediation in peripheral blood leukocytes. Conclusions: DNA methylation at specific genes may be mediators of associations between childhood socioeconomic disadvantage and mid-life BMI in adipose tissue. Findings motivate continued efforts to study if and how childhood socioeconomic disadvantage is biologically embedded at the level of the epigenome in regions etiologically relevant for adiposity. Abstract : Supplemental digital content is available in the text.